Revitalising Said Nursi's Spirituality Through Education as an Impact of Materialism - Tana, Alhini Zahra (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The objectives of this study are: (1) Knowing the urgency of spirituality in education according to Said Nursi, (2) Knowing the phenomenon of the decadence of spirituality caused by the spread of the paradigm of materialism, (2) Knowing the efforts to revitalize spirituality through education offered by Said Nursi. This research is library research that uses a library research approach with a type of philosophical research that uses a descriptive-qualitative approach. The data collection technique in this research is a literature study with Said Nursi's writings as the primary reference. At the same time, data analysis uses content analysis. The results of this study: 1) Knowing Said Nursi's thoughts on the urgency of spirituality in education, 2) Understanding the impact of the materialism paradigm on spirituality, 3) Understanding the solutions that modern society can do as a result of Said Nursi's revitalization of spirituality with alternative education. In conclusion, education is an important medium for Said Nursi to revitalize spirituality, which he considers to have decadence due to the rise of the materialism paradigm, which has directly changed the dynamics of the life of the community where he lives and Nursi's thinking is considered very relevant to be used as a reference in revitalizing spirituality in this era.